Risk factors of colorectal cancer – literature review - Urbańczyk, Agnieszka; Rutkowska, Julia; Skorek, Klaudia; Babiak, Rafał; Rzęsa-Tokarczyk, Żaneta; Bajak, Karolina; Gawęda, Agnieszka; Grabek, Agata; Czuchryta, Paulina; Domańska, Anastazja (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Colorectal cancer is one of the most common cancers in the world. It is very important to expand knowledge about this disease because it affects millions of people. Better understanding of the disease will help develop better prevention and treatment strategies. The aim of our work is to classify, analyze and describe colorectal cancer risk factors. This article was written based on articles found in the PubMed database. State of knowledge: Colorectal cancer risk factors can be divided into two groups: modifiable and unmodifiable. Modifiable factors include: diet, low physical activity, smoking, alcohol, overweight and obesity. Unmodifiable factors include: age, sex, inflammatory bowel diseases, genetic factors, family history of colorectal cancer. Each of them increases the risk of developing the disease, the risk is the greater the more factors are present simultaneously. Modifiable factors seem to play a greater role in the development of the disease than unmodifable factors. Summary: Studies of colorectal cancer risk factors may help in the development of prevention. It can also facilitate the personalization of preventive examinations and treatment. By influencing modifiable factors, we can reduce the risk of developing the disease, because following the principles of a healthy lifestyle can minimize the risk associated with genetic factors for the development of colorectal cancer.